PENGARUH KOMPETENSI MANDOR TERHADAP KUALITAS PELAKSANAAN KONTRUKSI GEDUNG DI MALANG RAYA - Youngky Pratama, Hariyono Seputro; Murni Dewi, Sri; Anwar, Ruslin (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Hariyono Seputro Youngky Pratama1, Sri Murni Dewi2 & Ruslin Anwar31, 2 & 3Jurusan Teknik Sipil, Fakultas Teknik, Universitas Brawijaya MalangAlamat Korspondensi: Jl.MT. Haryono 167, Malang 65145, IndonesiaE-mail: civil@brawijaya.ac.idABSTRACTThe purpose of this study was: (1) to analyze the factors that affect the competence of foremanon the quality of construction of the building performance in Malang. (2) to know the relationship ofvariables that affect the competence of supervisors on the performance of the quality of buildingconstruction in Malang. The research was carried out on several samples of foreman in Malang.The sampling technique used is the judgmental technique (purposive). The statistical tool used inthis study is Structural Equation Model (SEM) to determine the relationship of variables that affectthe foreman’s competence on the quality of construction of the building performance in Malang.The analysis showed that foreman’s competency factors affecting the performance of thequality of building construction in Malang are competency skills, personal and management. Fromthe result of this research noted that there is a significant effect between skills variables, personalvariables and management variable on the quality of buildings construction in Malang. Based onthese result, it is advisable to conduct further research for other types of work that can be seen inmore depth the competence of foreman.Keywords: foreman competence, quality of building construction